Variations in low-latitude middle atmospheric thermal structure during the 15 January 2010 solar eclipse - Taori, A.; Sathishkumar, S.; Gurubaran, S. (My University, 2010)
The altitude profiles of middle atmospheric temperatures are examined to study the effects of the solar eclipse on 15 January 2010 as it passed through the Indian longitudes. It was found that thermal structures exhibited strong inversion layers on the eclipse day, with large temperature deviations around 45, 50, 60, 75, 82 and 92 km altitudes compared to normal days. Fourier analysis revealed no significant changes in the gravity wave characteristics; however, the amplitudes of the observed waves were significantly higher (~ two times) compared to the normal days.
Keywords: Inversion layers; Middle atmosphere; Solar eclipse; Thermal structure